Food insecurity among university students at a German university: Impact on health, academic performance, and lifestyle during COVID-19 - Kötzsche, Maike; Arroyo-Izaga, Marta; Heil, Eleonore; Jordan, Irmgard; Teuber, Ramona; Torheim, Liv E. (Informa UK Limited, 2025)
Studies show that university students, especially food insecure students, were often negatively affected by the COVID-19 pandemic. For Germany, no data covers this time period, differentiating between food security statuses. We conducted a cross-sectional online survey (n = 562) between November and December 2021 at the Justus Liebig University Giessen, Germany, using the validated Food Insecurity Experience Scale to assess food (in)security. Our results affirm changes in academic performance, health and eating habits during the pandemic, with food insecure participants being more negatively affected. Preventive measures are needed to mitigate the adverse effects of crises, targeting all, but especially food insecure university students.